India in the Global and Regional Trade: Determinants of Aggregate and Bilateral Trade Flows and Firms' Decision to Export - T. N. Srinivasan; Vani Archana (Indian Council for Research on International Economic Relations (ICRIER), 2009)
This paper contributes to two strands of literature on empirical models of trade flows and trade policy. The first and the older strand is that of gravity models of bilateral trade flows going back to Hans Linneman (1966) and Tinbergen (1962) and its recent applications, particularly by Adams et al (2003) and De Rosa (2007) in analyzing the impact of Preferential Trade Agreements (PTAs). Our focus is on applying the gravity model to analyze India's trade flows (exports and imports) with its trading partners around the world and to examine the impact of various PTAs in which India or its trading partner or both are members. Clearly this is of interest, since, from 1991 India is aggressively negotiating and concluding PTAs of which South Asian preferential trade (and later free trade) agreement is the most prominent. We find that India is not well served by its pursuit of PTAs and should instead push for multilateral trade liberalisation by contributing to conclusion of the Doha round of negotiations with an agreement beneficial to all WTO members. The second and the more recent strand is the analysis of trade flows using data on exports of individual firms. It is well known that in all countries of the world relatively few firms participate in world trade, thus suggesting that characteristics of a firm (such as its size and productivity) are relevant besides country level barriers on trade matter for participation in world trade. This strand is rapidly growing. Ours is one of the very few attempts at modeling and estimating the decision of Indian firms on their participation using firm level data. The paper reports on our preliminary results. We have also collected primary data from a sample survey of firms to explore this issue deeper. While these data are yet to be fully analyzed, nevertheless some preliminary descriptive tables summarizing them are included in an Appendix.
Keywords: F13; F14; F21; 330; Non-discriminatory trade liberalisation; Gravity model; Intrabloc trade effect; Trade diversion; Trade creation; Firm heterogeneity; Probability of exporting; Export performance; Logit; Probit; Fixed effect; Random effect; Tobit model; firm-specific effect; sunk cost; Hazard model; Handelsliberalisierung; Regionale Wirtschaftsintegration; Handelseffekt; Internationaler Markteintritt; Sunk Costs; Gravitationsmodell; Schätzung; Indien